Wood & memory: Rebuild old Älvsborg Fortree’s protect facility - Ma, Hanxiao (My University, 2025)
Älvsborg is an important historical site in Gothenburg, but the current state of its preservation is concerning. The wooden roof added to the site not only partially obscures the historical appearance of the ruin, but also encourages destructive human activities. In light of this situation, the thesis proposes the reconstruction of a protective structure for the site, with an emphasis on maximizing the reuse of existing wooden materials from a sustainable development perspective. The core of the design focuses on utilizing the aesthetics and temporal value of reused wood to highlight the beauty of time passing and to strengthen the historical narrative atmosphere of the site. The design employs methods such as literature review, case studies, photo scanning, and image collaging to examine the compatibility between new and existing materials and the site. Through surveying, documentation, systematic analysis, drawing, and handcrafted modeling, information about existing materials is gathered and used as the basis for design decisions. Reclaimed wood from the site serves as a key medium, forging a close connection between people, time, and place. The final design features a roof inspired by the shape of a mast and a wooden walkway, echoing the nearby dock and Älvsborgsbron. The use of a tensile structure enables the large-span roof beams to be formed from small-sized recycled wood, minimizing the number of supporting columns and showcasing the original appearance of the site to the greatest extent. Both the roof structure and the walkway surface use reused timber from the existing wooden structure. Through measuring, documentation and classification of the materials, joint studies of the structure, details and connections were designed based on the shape and number of materials. Removable connection components, such as bolts and mortise-and-tenon joints, are used to facilitate the subsequent recycling and reuse of materials.
Keywords: Timber reuse, materiality, historical narratives, ruin preservation, multisensory experience